Profil Penderita Ablasio Retina Eksudatif di Klinik Mata SMEC Tahun 2019-2022 - Hazami, Lathifah Nur Islami B.; Fatmawati, Nur Khoma; Sawitri, Endang (Faculty of Medicine, Universitas Andalas, 2023)
Retinal detachment is a critical ocular condition arising from separating two retina layers, leading to an abrupt decline in visual acuity. Exudative retinal detachment occurs due to fluid accumulation from the inflammatory reaction. Objective: To ascertain the demographic characteristics of individuals diagnosed with retinal detachment at SMEC Eye Clinic in Samarinda from 2019 to 2022. Methods: This study was a cross-sectional descriptive study that utilized data from the available population. The sample comprises seven medical records of patients with exudative retinal detachment at SMEC Eye Clinic in Samarinda between 2019 and 2022. Results: The age range observed was six patients (85.7%) between the ages of 15-65 years and one patient (14.3%) > 65. The mean age of patients was 39,4 years. Among the patients, 6 (85.7%) female and 1 (14.3%) male. Unilateral eye involvement was observed in 6 patients (85.7%), while bilateral involvement was observed in 1 (14.3%). The most commonly observed accompanying eye disease was choroidal disorder. In contrast, the most commonly observed non-eye comorbidity was diabetes mellitus. Conclusion: Most exudative retinal detachment cases observed at SMEC Eye Clinic between 2019 and 2022 were concentrated within the age bracket of 15 to 65 years, with a higher proportion of female patients. The condition was predominantly unilateral, and the presence of comorbidities such as choroidal disorder and diabetes mellitus was also noted.Keywords: Â affected eye side, comorbidities, exudative retinal detachment, risk factors